Neurology and the Global HIV Epidemic - Meyer, Ana-Claire (Seminars in Neurology, 2014)
The vast majority of people living with human immunodeficiency virus (HIV) infection reside in resource-limited settings. As compared with resource-rich settings, there are important differences in the epidemiology and outcomes of HIV infection in resource-limited settings. Nonetheless, little HIV neurology research occurs in these regions. We will first review clinical, epidemiological, and translational HIV neurology research originating from resource-limited settings. We will then discuss the barriers to conducting neurologic research, such as limited human resources, diagnostics, and access to medications. Finally, we will review existing initiatives to build capacity for research in resource-limited settings. Despite the barriers, there is growing interest in and opportunities for collaborative international neurologic research. Including diverse viral and human populations from across the globe in research opens possibilities for important implementation science, clinically oriented science, and basic science discoveries.
Keywords: human immunodeficiency virus; global health; neurology; HIV-associated neurocognitive disorders